THE USE OF REALIA MEDIA-ASSISTED CONTEXTUAL TEACHING AND LEARNING MODEL TO IMPROVE MATHEMATICS LEARNING OUTCOMES ON FRACTIONAL LEARNING MATERIALS IN GRADE IV ELEMENTARY SCHOOL - Maria Shalvahana Mutiara; Yulia Linguistika; Siti Mas'ula (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the information related to the differences in students’ learning outcomes after applying the CTL model assisted by realia media and conventional models on fractional learning material in grade IV elementary school. The research uses a quantitative approach through the application of Quasi Experimental model with experimental methods and Nonequivalent Control Group Design. Class IV Sultan Agung and Class IV Sultan Hasanudin at SDN A Blitar were research samples. The classes are separated into two classes, the experimental class applying the CTL model assisted by realia media and the control class applying conventional models. The pretest and posttest scores in both classes are the analyzed data. SPSS 22 for Windows is used to help analyze data. The results indicate that the average posttest score of the experimental class was 53.6 exceeding the control class average score, which had a value of 29.92. The results, which obtained through data analysis from both classes, are said to be normal and homogeneous. The results, which obtained on the Wilcoxon test in the experimental class of 0.000 < 0.05, indicate a difference in results before and after treatment using an N-Gain Score at 0.3619. The control class Wilcoxon test results were 0.079 > 0.05, which imply that there is no difference before and after treatment with an N-Gain Score at 0.0661. The Mann-Whitney test produces significant values at 0.001 < 0.05, which indicate that learning outcomes through the application of realia media-assisted CTL models are different from conventional models.